Analysis of real time video traffic for enhanced distributed channel access over WLAN - Jama, Abdirisaq Mohammed; Khalifa, Othman Omran; Hamdan, Moussa Ali (2013)
This paper presents a study of an Enhanced Distributed Channel Access method (EDCA) in the IEEES02.11e standard and enhanced protocol. The protocol is evaluated under different network loads for real-time applications using MPEG-4 video traffic, and then compared with the earlier legacy IEEE 802.11 DCF access method. A Simulation using Network Simulator 2 (NS-2) & Evalvid were carried out using different performance metrics and applied various QoS parameters such as average end-to-end delay, throughput and packet loss ratio. Simulation results of throughput, decidable frame rate, PSNR, and packet loss, show good quality with lower packet loss and higher throughput.